Pengaruh Pemberian Probiotik dalam Pakan terhadap Pertambahan Bobot Badan Kambing Kacang - adriani, adriani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
This study was conducted to determine the effects of  probiotic in ration by body weight Kacang goat. This study  used 16 male goat with 1- 1.5 months of age at 10 – 20 kg of body weight. The design in this study was randomized block completely design with 4 treatments of probiotic  and  4  body weight as block. Each group received the experimental ration: without probiotic (K0),  0.25% of probiotic (K1), 0.50% of probiotic (K2) and 0.75% of probiotic (K3). Parameter measured were  dry matter intake, body weight and ration efficiency. Result of this study showed that there was no significant effect on drymatter intake, body weight and  ration efficiency The conclusion of this study was that the probiotik did not increase body weight and ration efficiency of kacang goat.